Pyramiding blast, bacterial blight and brown planthopper resistance genes in rice restorer lines - Zhi-juan JI; Shu-dong Yang; Yu-xiang ZENG; Yan LIANG; Chang-deng YANG; Qian QIAN (Journal of Integrative Agriculture, 2016)
Rice blast, bacterial blight (BB) and brown planthopper (BPH) are the three main pests of rice. This study investigated pyramiding genes resistant to blast, BB and BPH to develop restorer lines. Ten new lines with blast, BB and/or BPH resistance genes were developed using marker-assisted selection (MAS) technique and agronomic trait selection (ATS) method. Only HR13 with resistance genes to blast, BB and BPH was obtained. In addition to blast and BB resistance, four lines (HR39, HR41, HR42, HR43) demonstrated moderate resistance to BPH, but MAS for BPH resistance genes were not conducted in developing these four lines. These data suggested that there were unknown elite BPH resistance genes in the Zhongzu 14 donor parent. A more effective defense was demonstrated in the lines with Pi1 and Pi2 genes although the weather in 2012 was favorable to disease incidence. Blast resistance of the lines with a single resistance gene, Pita, was easily influenced by the weather. Overall, the information obtained through pyramiding multiple resistance genes on developing the restorer lines is helpful for rice resistance breeding.